On the Mechanism by which Cell Contact Induces the Release Reaction of Blood Platelets; the Effect of Cationic Polymers - Massini, P; Lüscher, E. F (Thrombosis and Haemostasis, 1972)
Human blood platelets are aggregated by the basic polymers polylysine and DEAE- dextran. Under certain conditions a second phase of aggregation, concomitant with the release reaction, is elicited. The presence of ADP, calcium ions and a plasmatic cofactor within the primary aggregates are necessary for the induction of the release reaction. These experiments demonstrate that cell contact per se does not lead to a release reaction ; in order to become effective it must take place in the presence of ADP.